Review: The Dark Side of Democracy: Explaining Ethnic Cleansing - Itamar Magid (Amsterdam Law Forum, 2010)
The Dark Side of Democracy: Explaining Ethnic Cleansing Michael Mann, Cambridge University Press 2005, 580 pages, ISBN: 978-0-521-53854-1